Evaluation of Emergency Assembly Areas with the AHP Method from the Perspective of Occupational Safety Experts - Onur Doğan (Doğal Afetler ve Çevre Dergisi)
Occupational safety specialists are people who identify possible dangerous situations in the workplace and implement protective and preventive practices to prevent these hazards from turning into risks. They also play an important role in determining emergency assembly areas. Since workplaces have a dynamic structure, events that require emergency situations can occur very often compared to residential units. Occupational safety specialists are experts and have a high level of competence in combating all kinds of negative effects (earthquake, sabotage, accident, fire, etc.) that may affect the business ecosystem. For this reason, it is thought that it will be important to benefit from the knowledge and experience of occupational safety experts in the determination of emergency assembly areas in settlements. This study was conducted to evaluate the assembly areas in emergency and disaster situations from the perspective of occupational safety experts. In the study, the Analytical Hierarchy Process (AHP) method, one of the Multi-Criteria DecisionMaking Methods (MCDM), was used. AHP is a method that incorporates objective and subjective views into the process. What makes this method superior to other MCDM methods is that it allows the inclusion of qualitative and quantitative elements in the process. In the study, the criteria and the sub-criteria related to these criteria were prepared by considering the literature research and the opinions of experts in the field and were applied face-to-face to the occupational safety experts. Microsoft Excel was used in the solution of the study and the results of each analysis were consistent. Accordingly, as a result of the comparison made between the criteria, the criterion with the highest weight was 0.4294 assembly area security, followed by 0.3602 assembly area access and 0.2104 assembly area characteristics, respectively